PEDAGOGICAL SUPPORT MECHANISMS IN TEACHING MATHEMATICS: SCAFFOLDING AS A LEARNING SUPPORT TECHNOLOGY - Shmigirilova, И.; Tadzhigitov, А.; Dutkin, М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2026)
This article examines scaffolding technology as an effective pedagogical support mechanism. Schoolchildren's acquisition of mathematics is fraught with significant challenges, the need to overcome which highlights the importance of scaffold support for students and the search for didactic tools that facilitate their gradual transition to independent learning. The aim of this study is to investigate the didactic potential of scaffolding technology and the conditions for its effective integration into the educational process in the context of mathematics instruction. The theoretical study analyzed and systematized the results of scientific and methodological research on educational scaffolding, complemented by a summary of pedagogical experience using this technology in mathematics instruction. The empirical phase of the study, which included a survey of mathematics teachers, revealed the specific perceptions of scaffolding among practicing teachers, as well as the methodological and organizational difficulties associated with their lack of preparedness for the practical use of scaffold support in the educational process. The findings and recommendations presented can be used to improve the effectiveness of pedagogical support methods for students and to develop teacher professional development programs